Tourists’ assessment on translation of object labels at Vietnamese women’s museum = Đánh giá của du khách nước ngoài về bản dịch các mẫu vật ở bảo tàng phụ nữ Việt Nam - Phạm, Thu Trang (2020)
This study primarily investigates tourists’ assessment of translation of object labels at Vietnamese Women’s Museum. Besides, their preferences for translation and recommendation are also explored. First and foremost, the paper presents the rationale and objectives of the research as well as the research questions. Then, the background knowledge of culture-related concepts and different approaches toward translation evaluation will be introduced. In the ensuing section, the study will focus on findings tourists’ assessment on translation at Vietnamese Women’s Museum by using such data collection instruments as questionnaire and interview and examine the data with quantitative and qualitative procedures. In addition, their preferences for translation strategies and procedures will also be analyzed by showing tourists the category of classified translation based on the model proposed by Vinay and Darbelnet (2000). Eventually, the researcher will summarize the findings and give some suggestions from the results